Dynamics of Host-Parasitoid Populations and Biological Control - Patanarapeelert1*, Nichaphat; Patanarapeelert2*, Klot (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
In this article, we propose the host-parasitoid model that takes into account the duration of developing to be the mature parasitoid after the eggs were laid in host and the effect of refuge in host population for hiding from predation. The existence of critical time delay for unstable coexist equilibrium is examined. The successful biological control to suppress the abundance of an insect pest causing damage to crops is also discussed. Keywords: Host, Parasitoid, Insects, Refuge, Time Delay, Biological Control *Corresponding author: E-mail: nichaphatb@kmutnb.ac.th